A method for preparing a composite coating for preventing hydrogen penetration of pipe fittings
By preparing the Y2O3/TiO2 composite coating on the pipe fittings and performing annealing treatment, the problem of crystal orientation changes of the oxide coating in high-temperature hydrogen permeation experiments was solved, and the hydrogen resistance and density of the coating were improved.
Patent Information
- Application Number
- CN202211707563.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-12-29
AI Technical Summary
In the prior art, the oxide coating will undergo crystal orientation changes during the high-temperature hydrogen permeation experiment, reducing the hydrogen resistance of the coating.
The preparation method of Y2O3/TiO2 composite coating is adopted, including surface polishing and cleaning of pipe fittings, deposition and annealing of Y2O3/TiO2 composite coating to improve the density and hydrogen resistance of the coating.
Through the preparation of Y2O3/TiO2 composite coating, the crystal orientation changes are avoided, the hydrogen resistance of the coating is improved, and the uniformity and density of the coating are achieved.
Smart Images

Figure CN116809360B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen permeation-resistant coatings for pipe fittings, and in particular to a method for preparing a hydrogen permeation-resistant composite coating for pipe fittings. Background Art
[0002] A nuclear power plant is an extremely complex and multi-system complex. The generation of tritium in the core and its diffusion into the primary coolant, coupled with complex environments such as high temperature and irradiation, can easily lead to hydrogen embrittlement of structural materials, causing safety accidents and radioactive contamination. In addition, the preparation technology of high-performance tritium barrier coatings on the inner wall of the helium-cooled solid tritium breeder blanket unit of the deuterium-tritium (DT) fusion reactor is a key technology to achieve tritium self-sustaining and tritium safety. Researchers and engineers from all over the world have developed a large number of hydrogen permeation barrier coatings using various coating preparation technologies. However, the complex unit circuit, especially in large-area engineering preparation technology, brings great difficulties to the preparation of inner wall tritium barrier coatings. Compared with traditional tritium barrier coating preparation technologies such as magnetron sputtering (PVD), chemical vapor deposition (CVD), embedding method (PC), hot dip method (HD) and electrochemical deposition method (EC), metal organic decomposition (MOD) technology uses a liquid phase method for preparation, which has the characteristics of being suitable for pipelines, low-temperature preparation and simple process. In addition, compared with the traditional sol-gel technology, the coating prepared by MOD technology has high density and is not prone to cracks and voids. Therefore, the preparation of tritium barrier coatings by MOD technology shows good application prospects.
[0003] In recent years, many research institutions have conducted a series of systematic studies on the MOD method, mainly focusing on the research of single oxide hydrogen barrier coatings, such as bait oxide, yttrium oxide and aluminum oxide. However, during the long-term hydrogen permeation process at 700℃, the above oxide coatings will undergo changes in crystal orientation, reducing the coating's ability to inhibit hydrogen permeation. For example, in the 700℃ hydrogen permeation experiment, the crystal orientation of the bait oxide coating was observed to change from {111} to {100}.
[0004] Therefore, it is necessary to develop a binary or even multi-component oxide coating to avoid crystal orientation transformation during high-temperature hydrogen permeation experiments and improve hydrogen barrier properties to solve the above-mentioned prior art problems. Summary of the invention
[0005] The present invention provides a method for preparing a composite coating for preventing hydrogen penetration of pipe fittings, which is used to solve the technical problem in the prior art that the crystal orientation of the oxide coating changes during a high-temperature hydrogen penetration experiment, thereby reducing the hydrogen penetration inhibition performance of the coating.
[0006] The technical solution of the present invention:
[0007] A method for preparing a hydrogen permeation-resistant composite coating for a pipe, comprising the following steps:
[0008] Step 1: Polishing and cleaning the surface of pipe fittings;
[0009] Step 2: Preparation of Y2O3 / TiO2 composite coating;
[0010] Step 3: The Y2O3 / TiO2 coating is annealed.
[0011] The step 1, polishing and cleaning the surface of the pipe fitting, comprises:
[0012] The inner surface of the pipe fittings was cleaned in the following order: first, ultrasonic alkaline cleaning with 5% NaOH at 50°C for 10 minutes; second, ultrasonic acid cleaning with 10% H2SO4 at 55°C for 20 seconds; finally, ultrasonic cleaning with deionized water, acetone, and alcohol for 20 to 30 minutes, and air drying; then the pipe was placed in the clamp of the lifting machine, and a 3-5 micron palladium film was deposited on the outer wall of the pipe fitting to prevent oxidation of the outer surface of the substrate during the baking process and hydrogen permeation process, and the coating deposition began;
[0013] The inner diameter of the tube is 4mm-15mm, the outer diameter is 5mm-20mm, and the minimum wall thickness is 0.3mm.
[0014] Step 2, preparation of Y2O3 / TiO2 composite coating, including: depositing Y2O3 / TiO2 composite coating on the inner surface of the pipe at room temperature using a homemade dual-temperature zone high-temperature pulling machine, the pulling machine has two independent temperature zones, the upper temperature limit is 600°C, and the pulling speed range is 0-200mm / min.
[0015] The preparation of the Y2O3 / TiO2 composite coating in step 2 also includes:
[0016] In the first time period, two metal organic decomposition liquids, commercial Y-03 and Ti-O3, were selected and mixed in an atomic molar ratio of 1:10, and sealed and stirred at 5-15°C for 4 hours to prepare a Y2O3 / TiO2 precursor solution;
[0017] In the second time period, the pulling speed of the coating is controlled within 50-120 mm / min, the volatilization temperature and time are maintained at room temperature for 10-15 minutes; the drying time is 10-15 minutes under the condition of a drying temperature of 100-120°C; the baking temperature range is 550-600°C, the baking time is controlled at 10-15 minutes, and the argon atmosphere is used to deposit the Y2O3 / TiO2 composite coating on the pipe by repeating the volatilization, drying and baking processes 100-200 times.
[0018] The step 3, annealing the Y2O3 / TiO2 coating, comprises:
[0019] The deposited coating is taken out from the pulling machine and placed in an ultra-high vacuum annealing furnace for annealing;
[0020] The annealing process parameters include: vacuum degree 10 -5 Pa, annealing temperature is 650-850℃, heating rate is 5℃ / min, keep warm for 30min, cool to room temperature and take out.
[0021] Beneficial effects of the present invention:
[0022] (1) Compared with traditional coating preparation techniques such as organic chemical vapor deposition, electrochemical deposition, and magnetron sputtering, the present invention has the advantage of preparing tritium barrier coatings for pipes with uniform coating thickness and dense coatings. In addition, the process flow of this method is simple, economical, and can be industrialized and mass-produced.
[0023] (2) The advantages of the present invention lie in the ratio of Y2O3 / TiO2 solution, the dense coating, and the good hydrogen barrier performance, which reduces or avoids the change of crystal orientation during the hydrogen permeation experiment.
[0024] (3) The present invention can control the thickness, morphology and structure of the coating by changing the pulling speed, baking temperature, annealing temperature and atmosphere; since the mechanical properties of the coating are better and it is not easy to cause mechanical failure, the hydrogen permeation resistance of the coating is better. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a sample diagram of the coating deposited on the pipe measured by the scratch method in Example 1 of the present invention;
[0026] Figure 2 This is a morphology diagram of the coating on the pipe in Example 2 of the present invention; DETAILED DESCRIPTION
[0027] The preparation method of a pipe hydrogen permeation barrier composite coating of the present invention is described in detail below with reference to the accompanying drawings and embodiments.
[0028] A method for preparing a hydrogen permeation-resistant composite coating for a pipe, comprising the following steps:
[0029] Step 1: Polishing and cleaning the surface of pipe fittings;
[0030] Step 2: Preparation of Y2O3 / TiO2 composite coating;
[0031] Step 3: The Y2O3 / TiO2 coating is annealed.
[0032] The step 1, polishing and cleaning the surface of the pipe fitting, comprises:
[0033] The inner surface of the pipe fittings was cleaned in the following order: first, ultrasonic alkaline cleaning with 5% NaOH at 50°C for 10 minutes; second, ultrasonic acid cleaning with 10% H2SO4 at 55°C for 20 seconds; finally, ultrasonic cleaning with deionized water, acetone, and alcohol for 20 to 30 minutes, and air drying; then the pipe was placed in the clamp of the lifting machine, and a 3-5 micron palladium film was deposited on the outer wall of the pipe fitting to prevent oxidation of the outer surface of the substrate during the baking process and hydrogen permeation process, and the coating deposition began;
[0034] The inner diameter of the tube is 4mm-15mm, the outer diameter is 5mm-20mm, and the minimum wall thickness is 0.3mm.
[0035] Step 2, preparation of Y2O3 / TiO2 composite coating, including: depositing Y2O3 / TiO2 composite coating on the inner surface of the pipe at room temperature using a homemade dual-temperature zone high-temperature pulling machine, the pulling machine has two independent temperature zones, the upper temperature limit is 600°C, and the pulling speed range is 0-200mm / min.
[0036] The preparation of the Y2O3 / TiO2 composite coating in step 2 also includes:
[0037] In the first time period, two metal organic decomposition liquids, commercial Y-03 and Ti-O3, were selected and mixed in an atomic molar ratio of 1:10, and sealed and stirred at 5-15°C for 4 hours to prepare a Y2O3 / TiO2 precursor solution;
[0038] In the second time period, the pulling speed of the coating is controlled within 50-120 mm / min, the volatilization temperature and time are maintained at room temperature for 10-15 minutes; the drying time is 10-15 minutes under the condition of a drying temperature of 100-120°C; the baking temperature range is 550-600°C, the baking time is controlled at 10-15 minutes, and the argon atmosphere is used to deposit the Y2O3 / TiO2 composite coating on the pipe by repeating the volatilization, drying and baking processes 100-200 times.
[0039] The step 3, annealing the Y2O3 / TiO2 coating, comprises:
[0040] The deposited coating is taken out from the pulling machine and placed in an ultra-high vacuum annealing furnace for annealing;
[0041] The annealing process parameters include: vacuum degree 10 -5 Pa, annealing temperature is 650-850℃, heating rate is 5℃ / min, keep warm for 30min, cool to room temperature and take out.
[0042] Example 1
[0043] The Y2O3 / TiO2 hydrogen permeation barrier coating is prepared on the inner surface of a 316 stainless steel tube using a high-temperature pulling machine, including the following process steps:
[0044] Step (1): Polishing and cleaning of pipe surface
[0045] First, clean the inner surface of the tube in the following order: 1) ultrasonic alkaline cleaning with 5% NaOH at 50°C for 10 minutes; 2) ultrasonic acid cleaning with 10% H2SO4 at 55°C for 20 seconds; 3) ultrasonic cleaning with deionized water, acetone, and alcohol for 20 to 30 minutes, and then blow drying.
[0046] Step (2): Preparation of Y2O3 / TiO2 composite coating
[0047] A Y2O3 / TiO2 composite coating was deposited on the substrate surface at room temperature using a dual-temperature zone high-temperature puller. The puller had two independent temperature zones, both with a temperature upper limit of 600°C and a pull speed zone upper limit of 200 mm / min. The coating deposition process included the following four continuous time periods:
[0048] (a) In the first time period, two metal organic decomposition solutions, Y-03 and Ti-O3, were selected and mixed in an atomic molar ratio of 1:10, and sealed and stirred at 5-15°C for 4 h to prepare a Y2O3 / TiO2 precursor solution.
[0049] (b) In the second process step, the pulling speed of the coating is controlled within 50-120 mm / min, and the number of pulling times is within 200 times to obtain a coating with higher surface quality. Determination of baking temperature: When the temperature is lower than 550°C, the organic matter is not completely decomposed, and the coating contains more carbon elements, which causes the coating to peel off during the annealing process. However, when the temperature is too high (>650°C), the substrate is obviously oxidized, and the formation of iron oxide will reduce the hydrogen barrier performance of the coating. In addition, if the pulling speed is too slow, the coating preparation time will be greatly extended. In summary, the process parameters of the high-temperature pulling machine are set as pulling speed: 50 mm / min; volatilization temperature and time: room temperature and 10 minutes; drying temperature and time: 120°C and 10 minutes; baking temperature and time: 550-650°C and 15 minutes; repeat the volatilization, drying and baking processes 100-200 times.
[0050] Step (3): annealing of the Y2O3 / TiO2 coating
[0051] The deposited coating is taken out from the pulling machine and placed in an ultra-high vacuum annealing furnace for annealing. The specific annealing process parameters are as follows: vacuum degree 10-5Pa, annealing temperature 650-850℃, heating rate 5℃ / min, heat preservation for 3h, and then taken out after cooling to room temperature.
[0052] Finally, the coating prepared in Example 1 was subjected to performance testing, including the following test processes, indicators and results:
[0053] (1) The coating phase structure was measured using a DX-2700 X-ray diffractometer (XRD). The test parameters were: tube voltage 22 kV, tube current 6 mA, Cr target K radiation. The results showed that the diffraction peaks belonged to titanium oxide and yttrium oxide, and no diffraction peaks of the substrate oxide were observed.
[0054] (2) Using the scratch method, as shown in the attached Figure 1 There is no peeling at the edge of the scratch and the bonding force is greater than 100N.
[0055] (3) The hydrogen permeation tester used was used to evaluate the hydrogen permeation resistance of the coating. The test parameters were: the permeation gas was D2 gas, the permeation temperature was 500°C, and the back vacuum was ≤5×10-5Pa. The results showed that the hydrogen permeation resistance factor of the Y2O3 / TiO2 coating was >100.
[0056] Example 2
[0057] The coating performance is related to the type of steel substrate. Therefore, in this embodiment, a high-temperature puller is used to prepare a Y2O3 / TiO2 hydrogen permeation barrier coating on the inner surface of a Fe-Cr-Ni (iron-based material containing 18%-20% Cr and 18%-25% Ni) pipe. Compared with Example 1, the following process conditions are different:
[0058] (1) Different from step (1) in Example 1, after the substrate is dried, it is annealed in a vacuum furnace at a temperature of 700°C and a vacuum degree of 10-3Pa for 3 hours to allow the chromium element of the substrate to diffuse to the surface of the substrate, and then oxidized at 500°C for 1 hour under a vacuum degree of 1Pa to form a dense chromium oxide film on its surface, thereby further improving the surface quality and hydrogen barrier properties of the coating.
[0059] (2) Different from step (1) in Example 1, a Fe-Cr-Ni stainless steel tube is used as the substrate.
[0060] (3) The difference from step (1) in Example 1 is that the concentration of sulfuric acid is diluted from 10% to 8%.
[0061] (4) Different from step (2) in Example 1, the number of pulling times is 200 times.
[0062] Except for the above, other process parameters are the same. The coating performance test method is the same as that in Example 1. The results show that the surface of the Y2O3 / TiO2 hydrogen permeation barrier coating is dense and smooth, and no obvious cracks or other defects are observed (see Appendix). Figure 2 ); The hydrogen permeation resistance factor of the coating is >200.
[0063] The embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the field without departing from the purpose of the present invention.
Claims
1. A method for preparing a hydrogen permeation-resistant composite coating for pipes, characterized in that: The steps include: Step 1: Polishing and cleaning the surface of pipe fittings; Step 2: Preparation of Y2O3 / TiO2 composite coating; Step 3: The Y2O3 / TiO2 coating is annealed.
2. The method for preparing a hydrogen permeation barrier composite coating for pipes according to claim 1, characterized in that: The step 1, polishing and cleaning the surface of the pipe fitting, comprises: The inner surface of the pipe fittings was cleaned in the following order: first, ultrasonic alkaline cleaning with 5% NaOH at 50°C for 10 minutes; second, ultrasonic acid cleaning with 10% H2SO4 at 55°C for 20 seconds; finally, ultrasonic cleaning with deionized water, acetone, and alcohol for 20-30 minutes, and air drying; then the pipe was placed in the clamp of the pulling machine, and a 3-5 micron palladium film was deposited on the outer wall of the pipe fitting to prevent oxidation of the outer surface of the substrate during the baking process and hydrogen penetration process, and the coating deposition began; The inner diameter of the pipe is 4mm-15mm, the outer diameter is 5mm-20mm, and the minimum wall thickness is 0.3mm.
3. The method for preparing a hydrogen permeation barrier composite coating for pipes according to claim 1, characterized in that: Step 2, preparation of Y2O3 / TiO2 composite coating, including: depositing Y2O3 / TiO2 composite coating on the inner surface of the pipe at room temperature using a homemade dual-temperature zone high-temperature pulling machine, the pulling machine has two independent temperature zones, the upper temperature limit is 600°C, and the pulling speed range is 0-200mm / min.
4. The method for preparing a hydrogen permeation barrier composite coating for pipes according to claim 1, characterized in that: The preparation of the Y2O3 / TiO2 composite coating in step 2 also includes: In the first time period, two metal organic decomposition liquids, commercial Y-03 and Ti-O3, were selected and mixed in an atomic molar ratio of 1:10, and sealed and stirred at 5-15°C for 4 hours to prepare a Y2O3 / TiO2 precursor solution; In the second time period, the pulling speed of the coating is controlled within 50-120 mm / min, the volatilization temperature and time are maintained at room temperature for 10-15 minutes; the drying time is 10-15 minutes under the condition of a drying temperature of 100-120°C; the baking temperature range is 550-600°C, the baking time is controlled at 10-15 minutes, and the argon atmosphere is used to deposit the Y2O3 / TiO2 composite coating on the pipe by repeating the volatilization, drying and baking processes 100-200 times.
5. The method for preparing a hydrogen permeation barrier composite coating for pipes according to claim 1, characterized in that: The step 3, annealing the Y2O3 / TiO2 coating, comprises: The deposited coating is taken out from the pulling machine and placed in an ultra-high vacuum annealing furnace for annealing; The annealing process parameters include: vacuum degree 10 -5 Pa, annealing temperature is 650-850℃, heating rate is 5℃ / min, keep warm for 30 min, cool to room temperature and take out.
Citation Information
Patent Citations
Multifunctional alumina / metal micro-laminated coating
CN101629028A
Process for low-temperature preparation of Zr-doped alpha-Al2O3 nanometer multilayer tritium barrier coating based on Cr2O3 template
CN106567050A